Provinciale Dienst voor Cultuur - Jaarverslag 1976. - Provincie West-Vlaanderen (Brugge : Provinciale Dienst voor Cultuur, 1978)
Van Anderlecht, Engelbert ; Bervoets, Freddy ; De Brune, Joost ; Clicque, Robert ; De Keyser, Raoul ; Leblanc, Walter ; Swimberghe, Gilbert ; Verbeke, Ludo ; Willaert, Joseph ; Dries, Jan ; Van Hoeydonck, Paul ; Holmens, Gerard ; Jans, Jos ; Martens, Michel ; Pas, Wilfried ; Timmer, Jan ; Copers, Loe ; Hoorne, Emiel ; Van Severen, Dan ; etc.
Nederlands
boek